Columbo. Season two [videorecording (DVD)]. - Falk, Peter, 1927-2011 (Universal Studios Home Entertainment, 2012)
Join Peter Falk as wry and ruffled Lieutenant Columbo as he solves L.A.'s most puzzling crimes with his trademark wit and style. In the smart, funny, and exciting second season of Columbo.